Strategi Guru dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam: Teachers’ Strategies in Enhancing Students’ Learning Motivation in Islamic Education - Muhammad Iqbal; Zaki Ulien Nuha (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2026)
This study aims to identify and analyze teacher strategies for increasing student learning motivation in Islamic Religious Education (PAI). The focus of the study is on how teachers design, implement, and evaluate learning approaches that encourage active participation and student interest. The research method used was descriptive qualitative through observation, interviews, and documentation studies of PAI teachers and students. The results indicate that the use of a variety of learning methods, such as discussions, inspirational stories, audiovisual media, and positive reinforcement, significantly contribute to increasing learning motivation. Teachers also employ a personalized approach to understand students' needs and characteristics. The study's conclusions confirm that creative, communicative, and student-centered learning strategies can create a more engaging and effective learning environment in increasing student learning motivation in PAI.